Microglia is associated with p-Tau aggregates in the olfactory bulb of patients with neurodegenerative diseases - Carmona-Abellan, Mar; Martinez-Valbuena, Ivan; Marcilla, Irene; DiCaudo, Carla; Gil, Isabel; Nuñez, Jorge; Luquin, Maria-Rosario (Neurological sciences, 2021)
The olfactory bulb (OB) seems to be the first affected structure in neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and Lewy body dementia (LBD). Deposits of protein aggregates, increased dopaminergic neurons, and decreased cholinergic inputs have all been described in the OB of these diseases. We investigated here the contribution of the activated microglial cells to the increased deposits of protein aggregates. We quantified the number of activated microglial cells and astrocytes in the OB of patients with histological diagnosis of PD ( n = 5), AD ( n = 13), and LBD ( n = 7) and aged-matched controls ( n = 8). Specific consensus diagnostic criteria were applied for AD, LBD, and PD. Protein aggregates were scored in the OB as grade 0, none; grade 1, mild; grade 2, moderate; and grade 3, severe. OB sections from the 33 subjects were stained with specific antibodies markers for reactive astrocytes (GFAP) and microglial cells (Iba1 and HLA-DR). The total number of Iba1-ir (Iba-immunoreactive) and HLAD-DR cells was estimated by stereological analysis, while quantification of astrocytes was performed by GFAP optical density. Statistical analysis was done using the Stata 12.0 software. The number of microglia and activated microglia cells (HLA-RD-ir) was increased in patients with neurodegenerative diseases ( p < 0.05). Moreover, the density of GFAP-ir cells was higher in the OB of patients. Neither the number of microglia cells nor the density of astrocytes correlated with the number of b-amyloid and alpha-synuclein deposits, but the density of Iba1-ir cells correlated with the number of p-Tau aggregates. Activated microglial cells and reactive astrocytes are present in the OB of patients with neurodegenerative diseases. The lack of correlation between the number of activated microglia cells and protein deposits indicate that they might independently contribute to the degenerative process. The presence of microglia is related to phosphorylated Tau deposits in neurodegenerative diseases.